Survey of Sugar Levels and Blood Pressure in Outdoor and Indoor Workers - Herrywati Tambunan; Dewi Maritalia; Nuraina Nuraina (GLOBAL HEALTH SCIENCE GROUP, 2024)
Patients with hypertension and diabetes in Indonesia tend to increase every year. Diet and activity patterns are one of the factors causing the disease in addition to heredity. This study aims to determine the level of sugar and blood pressure in workers in open and closed spaces. The sampling technique uses quota sampling, namely 100 respondents who work in open spaces and 100 respondents who work in closed spaces. The instrument used to measure blood pressure is a digital tension meter and to measure blood sugar levels using an easy touch glucometer, both measurements are taken on the same day for each respondent. Data collection was carried out for approximately 3 months, from August to November 2024 in Bireuen Regency. The results of the study were obtained by univariate and bivariate data analysis, univariate results obtained the majority of respondents' age in closed rooms 38-52 years (50%), open spaces 39-53 years (51%). The history of hypertension of respondents in the closed room has no history (78%), open space has no history (68%). There was no history of diabetes in the closed room (68%), no history in the open room (82%), the frequency distribution of respondents' pressure in the closed room (84%) was normal, in the open room (74%) was normal. The results of the examination of blood sugar levels of respondents in the closed room were normal (94%), in the open room normal (77%). The results of bivariate analysis with SPSS through Independent T test for blood pressure of workers in closed and open spaces there is no significant difference with a value of 0.072 (>0.05), and there is a significant difference between blood sugar levels of workers in closed spaces and workers in open spaces with a value of 0.000 (<0.05). Conclusion: the majority of blood pressure and blood sugar levels are within normal limits and there are differences in blood sugar levels between workers in closed spaces and workers in open spaces.